Multinational capital, public utilities, and urban change in Late Ottoman Istanbul: Constantinople tramway and electric company. - Ülker, Erol (Deutsches Institut für Urbanistik, 2018)
Der Beitrag untersucht die Infrastrukturentwicklung in der osmanischen Hauptstadt. Der Autor stellt die elektrische Straßenbahn und die Stromversorgung Istanbuls in den Mittelpunkt, die Anfang des 20. Jahrhunderts aufgebaut und schnell zu einem unentbehrlichen Bestandteil des hauptstädtischen Lebens wurden. Ausländische Investitionen waren unerlässlich für diese Entwicklung, führten aber auch zu einer Verschuldung der Betreibergesellschaft, was negative Auswirkungen auf den Betrieb hatte.

As a global tendency that accelerated in the last quarter of the nineteenth century, electricity gradually permeated almost every aspect of urban life, transforming the whole infrastructure of modern cities, from lightening to heating, transportation to communication and industrial production. This essay aims to provide insights about how this global process was experienced in Istanbul, the Ottoman Empire's capital city, during the initial decades of the twentieth century. To that end, the author concentrates on the Belgian-registered Constantinople Tramway and Electric Company, which invested in the energy and transport infrastructure of Istanbul. The formation of this multinational holding was a crucial aspect of urbanization in Istanbul. This process was closely associated with and the direct outcome of the development of the electric utility industry in Istanbul and the electrification of the city's tramway network.
Keywords: Stadtgeschichte; Stadtforschung; Sozialwandel; Moderne; Großstadt; Stadtverkehr; Straßenbahn; Verkehrsinfrastruktur; Stromversorgung; Technische Infrastruktur; Modernisierung